A synopsis of the apocryphal nativity and infancy narratives - Elliott, J. K. (New Testament tools and studies,, 2006)
Early Christians built on the stories of Jesus' birth found in the New Testament. Their later accounts, many of them found nowadays among collections of non-canonical ('apocryphal') texts, are important and interesting. They give insights into the growth of Christian theology, especially concerning the role and status of Mary, and also the way in which the earliest stories were elaborated and interpreted in popular folk religion. A range of the earliest accounts is presented here in fresh translations; it includes some rare Irish material. The texts are arranged in small units and synoptically, in order to permit readers to compare texts and to see the differences and similarities between them. J.K. Elliott has selected and arranged the texts, and he provides an introductory chapter to the genre. He also includes a full and helpful bibliography to benefit readers who may wish to pursue this comparative study more deeply.